PENGARUH PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA - Siti Umi Hanik; Suciati Muanifah (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the impact of tax planning on earnings management in companies listed on the Indonesia Stock Exchange (IDX). Financial reports produced by companies are vital tools for management to report their financial position and performance to external parties, including earnings management. Earnings management is often used as a strategy to achieve specific financial goals by manipulating figures in financial reports. Proper tax planning is expected to reduce the tax burden that the company has to pay and support efficient earnings management. This study found that tax planning has a significant influence on earnings management practices, depending on the industry sector of the analyzed company. In some cases, companies with good tax planning tend to have more efficient earnings management, while in other sectors, its influence is smaller or even negative. The findings of this study provide a clearer picture of how tax planning can influence strategic decisions related to earnings management.